FATORES DE RISCO ASSOCIADOS À NEFROLITÍASE RECORRENTE VIA REGRESSÃO LOGÍSTICA BINÁRIA - PETTERLE, Ricardo Rasmussen; BARBOZA, Lucas Antonio Serur; CARVALHO, Maurício (Brazilian Journal of Biometrics, 2017)
Nephrolithiasis is one of the most common diseases of the urinary tract and its incidence has been increasing over the past years. It affects 10 to 15% of the population and it is more prevalent between the third and fifth decades of life. Beyond the clinical effects, nephrolithiasis also has a substantial economic impact. In Brazil, data from Unified Health System (Sistema Único de Saúde, SUS) showed that in 2010 approximately R$ 30 million was expended in hospital admissions related to urinary lithiasis. For this reason, a better understanding of the factors related to nephrolithiasis will improve the prevention and treatment of this condition. The aim of the current study was to model the probability of recurrent nephrolithiasis from anthropometric measures, body composition, blood chemistry, insulin resistance and 24-hours urine analysis. All the data were collected in the Outpatient Nephrolithiasis Clinic from the Hospital de Clínicas, at Federal University of Paraná, Brazil. Applying a model of binary logistic regression analysis, we were able to identify that patients with higher blood glucose, high levels of uric acid in urine and with higher percentage of body fat showed a significantly increased probability of developing kidney stones. These findings illustrate the importance of a healthy lifestyle in the maintenance of adequate glycemic control and body composition.